2000
DOI: 10.1116/1.1320804
|View full text |Cite
|
Sign up to set email alerts
|

Thin SiO2 layers on Si(111) with ultralow atomic step density

Abstract: The morphologies of the oxide surface and of the Si–SiO2 interface that form on special Si(111) substrates have been studied by atomic force microscopy (AFM). The substrates are totally free of atomic steps or have very low step density. Step-free regions are formed on patterned Si(111) by thermal processing. AFM scans of the same areas prior to oxidation, after oxidation, and after chemical removal of the oxide allow the relative roughnesses to be compared. The step structure of the Si(111) substrate is trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The largest step-free areas were terraces with a width of approximately 30 µm. Oliver et al [66] used AFM to investigate the change of morphology of stepped surfaces due to oxidation. They found that the oxidation of silicon, i.e.…”
Section: Monoatomic Silicon Steps For Calibration Of Microscopesmentioning
confidence: 99%
“…The largest step-free areas were terraces with a width of approximately 30 µm. Oliver et al [66] used AFM to investigate the change of morphology of stepped surfaces due to oxidation. They found that the oxidation of silicon, i.e.…”
Section: Monoatomic Silicon Steps For Calibration Of Microscopesmentioning
confidence: 99%
“…12. It has been shown that once a clean surface with atomic steps and terraces is formed, the pattern of atomic steps on a Si substrate is preserved at the SiO 2 /Si interface after oxide formation. [13][14][15][16][17] For example, Oliver and Blakely 17 observed both the atomic steps on the original Si͑111͒ substrate and surface of oxide of 7 nm by AFM and found that they coincide within ϳ30 nm. Based on the present results, we suggest that the surface morphology is stable against oxidation also for gate oxidation of RCA-treated substrates.…”
mentioning
confidence: 99%